2020
DOI: 10.1038/s42003-020-01339-9
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal trafficking mediated by Arl8b and BORC promotes invasion of cancer cells that survive radiation

Abstract: Enhanced invasiveness, a critical determinant of metastasis and poor prognosis, has been observed in cancer cells that survive cancer therapy, including radiotherapy. Here, we show that invasiveness in radiation-surviving cancer cells is associated with alterations in lysosomal exocytosis caused by the enhanced activation of Arl8b, a small GTPase that regulates lysosomal trafficking. The binding of Arl8b with its effector, SKIP, is increased after radiation through regulation of BORC-subunits. Knockdown of Arl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 71 publications
1
24
0
Order By: Relevance
“…Instead, repurposing FDA approved drugs with P-glycoprotein inhibitory properties might prove more useful ( Lai et al, 2020 ). Furthermore, recent lines of evidence show that the mechanism by which some cancer cells become resistant to radiation is associated with lysosomal exocytosis, which is enhanced by the activity of Arl8b ( Wu et al, 2020 ). High levels of Arl8b and BORC subunit genes is indeed correlated with a poor prognosis in breast cancer, and knockdown of these genes decreases the survival and invasiveness of cancer cells.…”
Section: Lysosomal Dysfunctions Related Diseases and Therapeuticsmentioning
confidence: 99%
“…Instead, repurposing FDA approved drugs with P-glycoprotein inhibitory properties might prove more useful ( Lai et al, 2020 ). Furthermore, recent lines of evidence show that the mechanism by which some cancer cells become resistant to radiation is associated with lysosomal exocytosis, which is enhanced by the activity of Arl8b ( Wu et al, 2020 ). High levels of Arl8b and BORC subunit genes is indeed correlated with a poor prognosis in breast cancer, and knockdown of these genes decreases the survival and invasiveness of cancer cells.…”
Section: Lysosomal Dysfunctions Related Diseases and Therapeuticsmentioning
confidence: 99%
“…Moreover, PLK1 has been shown to play a role in TNBC progression, metastasis, and resistance [39][40][41]. A study by Wu et al (2020) showed that lysosomal trafficking mediated by ARL8B promotes invasion of BC and is associated with poor survival outcomes [42], which was also confirmed by another study in both BC and prostate cancer [43].…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies revealed that SAFB2 could be a biomarker in breast and renal cell cancers [ 42 , 43 ]. ARL8B is a pivotal regulative gene of lysosomal location; a prior study demonstrated that the expression of ARL8B is closely correlated with the prognosis of breast cancer patients [ 44 ]. Knockdown of VPS18 could repress the progression of glioma through sponging miR-370 [ 45 ].…”
Section: Discussionmentioning
confidence: 99%